PENERAPAN MEDIA ”PAHADAK” PAPAN KOTAK HAK DAN KEWAJIBAN UNTUK MENINGKATKAN PEMAHAMAN SISWA SEKOLAH DASAR KELAS IV MATERI PPKn SD Negeri 065853 Medan - Morita Br Manurung; Ismail Saleh Nasution (STKIP Subang, 2024)
The aim of this research is to increase students' understanding of SDN 065853 Medan in the PPKn Education area, especially in the area of ​​Rights and Obligations at Home and at School. This research involves the use of the media